2022
DOI: 10.1136/bmjqs-2021-014529
|View full text |Cite
|
Sign up to set email alerts
|

Optimising GPs’ communication of advice to facilitate patients’ self-care and prompt follow-up when the diagnosis is uncertain: a realist review of ‘safety-netting’ in primary care

Abstract: BackgroundSafety-netting has become best practice when dealing with diagnostic uncertainty in primary care. Its use, however, is highly varied and a lack of evidence-based guidance on its communication could be harming its effectiveness and putting patient safety at risk.ObjectiveTo use a realist review method to produce a programme theory of safety-netting, that is, advice and support provided to patients when diagnosis or prognosis is uncertain, in primary care.MethodsFive electronic databases, web searches,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 126 publications
1
26
0
Order By: Relevance
“…Safety netting has come to be regarded as ‘best practice’ in relation to cancer diagnosis, especially in non-specialist settings 41 42. Its aim is to ensure patients do not drop through the healthcare net but are monitored until symptoms are explained, defined as a consultation technique to communicate uncertainty, provide patient information on red-flag symptoms and plan for future appointments to ensure timely re-assessment of a patient’s condition 43.…”
Section: Safety Nettingmentioning
confidence: 99%
“…Safety netting has come to be regarded as ‘best practice’ in relation to cancer diagnosis, especially in non-specialist settings 41 42. Its aim is to ensure patients do not drop through the healthcare net but are monitored until symptoms are explained, defined as a consultation technique to communicate uncertainty, provide patient information on red-flag symptoms and plan for future appointments to ensure timely re-assessment of a patient’s condition 43.…”
Section: Safety Nettingmentioning
confidence: 99%
“…Realist reviews have been used to ‘diagnose’ problems and better understand a wide range of complex practices and interventions in the quality and safety field, from junior doctors’ antimicrobial prescribing1 to ‘safety-netting’ in primary care 2. The ultimate aim in a realist review project is typically focused on identifying solutions to complex problems, by developing theory-informed responses in the form of recommendations or new intervention designs.…”
Section: The Situation In Practicementioning
confidence: 99%
“…Realist reviews aim to produce a type of theory known as ‘programme theory’—a theory that explains what a programme or intervention is expected to do, and how it is expected to work 4. For example, Friedemann Smith et al ’s programme theory of safety-netting in primary care settings demonstrates the important contexts, mechanisms and range of outcomes involved when this intervention is successful in its aim to ensure patient safety 2. Recommendations for policy, practice and intervention design can be informed by the understanding captured in a programme theory.…”
Section: Realist Reviews: What Makes Them Different?mentioning
confidence: 99%
See 1 more Smart Citation
“…A literature review in 2019 reported the most common type of safety-netting article was an expert opinion (n=25), followed by qualitative studies (n=12), with no completed randomised controlled trial (RCT) 6. An updated realist review in 2022, which produced 15 recommendations to enhance the communication of safety-netting advice, included reference to two randomised trials, but neither had a primary intervention of safety-netting or referred to this term 7…”
mentioning
confidence: 99%